Mission Specific Solar Radiation Environment Model (MSSREM): Peak Flux Model - Z. D. Robinson; J. H. Adams Jr.; J. H. Fisher; J. H. Nonnast; D. C. Terry (Space Weather)
Abstract Coronal mass ejections and solar flares can accelerate high fluxes of energetic particles. Depending on where this solar activity occurs on the sun, these outward moving particles can reach the Earth and enter the Earth's magnetosphere. They can also strike manmade objects in space. If the electronics in space are not protected from these energetic particles, they can cause the spacecraft to reboot, go into “safe mode,” have other anomalies, or cause catastrophic damage and loss of the mission. To protect the mission, the user can employ one or more mitigation strategies. The user may choose to add shielding, choose parts less prone to radiation effects, and/or mitigate by design. Implementing any of these strategies adds cost to the mission, so it is important to frame the design for the purpose of survival in a reference environment, which is severe enough to provide the desired confidence of mission success, but not more. For this reason, models have been developed that construct a design reference environment tailored to a specific mission. In this paper, the Mission Specific Solar Radiation Environment Model (MSSREM) peak flux model will be discussed. MSSREM uses probabilistic modeling techniques to build a design reference environment that can be tailored to a user specified mission start date, mission duration, and confidence level. The model can be run for any space mission outside the Earth's magnetic field and 1 AU from the sun during the years 1953–2055.